Radiofrequency ablation of ventricular premature contraction originating from a native coronary cusp after transcatheter aortic valve replacement. Issue 6 (29th September 2017) - Tohoku, Shota; Hiroshima, Kenichi; Kuramitsu, Shoichi; Nagashima, Michio; Fukunaga, Masato; An, Yoshimori; Ando, Kenji
Abstract: We describe a case of radiofrequency ablation of ventricular premature contraction (VPC) originating from the left ventricular outflow tract after transcatheter aortic valve replacement. The VPC origin was the native aortic valve annulus between the left and right coronary cusps. Radiofrequency ablation was successfully performed by manipulating the ablation catheter from the gap between the sinotubular junction and implanted valve.